PROYEKSI KEBUTUHAN KONSUMSI PANGAN BERAS DI DAERAH ISTIMEWA YOGYAKARTA - Abdul Rohman; Artita Devi Maharani (Caraka Tani: Journal of Sustainable Agriculture, 2017)
Rice is a staple food for society.Rice consumption in Indonesia is relatively high compared to ASEAN countries, which is 114 kg/year. The importance of rice for the society leads the government to provide rice in order to avoid food insecurity due to lack of food supply. To anticipate the increasing needs of food, the projection of rice consumption demand in the future is required. This research was a descriptive research using quantitative approach. The aim of this research was to obtain the prediction or projection of rice consumption demand in Yogyakarta Special Region. Data of rice consumption demand were collected from Department of Food Security and Counseling Agency of Yogyakarta. Data were analyzed using trend analysis by projecting past trends using regression analysis model. The trend analysis shows that rice consumption demand in Yogyakarta is increasing, therefore the strategy is required to fulfill rice supply in the future by prioritizing the production in food production centers.